The mechanism of stab resistance of carbon fiber reinforced polymer. (December 2022) - Du, Zhe; Chen, Changjie; Wang, Xinhou
Highlights: A high-speed camera was used to observe the damage morphology of the material backside during puncture. Puncture threshold load representing material penetration is usually located at the initial loss position of material stiffness. The hardness and thickness of the material can be used to characterize the relationship between displacement and puncture force. The impact energy increase will lead to a rise in puncture depth and damage surface, but the failure mode remains unchanged. Abstract: In this paper, the puncture resistance of carbon fiber reinforced polymer (CFRP) with different thicknesses under various puncture energy was studied by in-situ observation. The puncture failure process of CFRP was analyzed using a high-speed camera and thin-film pressure sensor in terms of damage image and local pressure change. The experimental results show that the puncture threshold load (PTL) representing material penetration is usually located at the initial loss position of material stiffness. The penetration load can be divided into linear growth and delamination failure zones. Image localization was used to mark the puncture feature points on the puncture force–displacement curve to help characterize the puncture failure process. The theoretical equations of puncture force and displacement before material penetration are proposed and verified by introducing yield stress and friction force, and the correlation between the material thickness and the puncture resistance was proved. In addition, the failure modes and fracture morphology of CFRP after puncture are analyzed and summarized. After puncture impact, fiber fracture, pull out and slip deformation under the action of tensile force and cutting force, and matrix fracture and peel damage. The increase of impact energy leads to a broader range of impact damage but does not change the failure modes.